Isolation, Characterization, and Evaluation of Native Rhizobacterial Consortia Developed From the Rhizosphere of Rice Grown in Organic State Sikkim, India, and Their Effect on Plant Growth - Sherpa, Mingma Thundu; Sharma, Laxuman; Bag, Niladri; Das, Sayak (Frontiers in Microbiology, 2021)
Eight rhizospheric bacteria were isolated from the organic paddy fields of Sikkim, India, and identified as Pseudomonas kribbensis KSB, Burkholderia cenocepacia SRD, Kosakonia oryzendophytica YMA7, Pseudomonas rhodesiae SRB, Bacillus sp. ARA, Paenibacillus polymyxa COW3, Bacillus aryabhattai PSB2, and Bacillus megaterium PSB1. They showed plant growth-promoting attributes in rice and have bio-control potential against phytopathogen Colletotrichum gloeosporioides of large cardamom (Amomum subulatum). Burkholderia cenocepacia SRD showed production of indole acetic acid and ammonia and solubilization of phosphate and potassium and also possessed nitrogen fixation potential. It showed antagonistic activity against two other plant pathogens of large cardamom, viz., Curvularia eragrostidis and Pestalotiopsis sp., under in vitro conditions. The liquid bacterial consortium was prepared using the bacterial strains SRB, PSB1, and COW3 (Consortia-1); PSB2, SRD, and COW3 (Consortia-2); and COW3, KSB, and YMA7 (Consortia-3) to increase the growth and yield of rice plants under organic farming conditions. Greenhouse and field studies showed that the Consortia-3 had the highest plant growth-promoting activity. Consortia-3 demonstrated better agronomic performance in terms of root length (9.5 cm),number of leaflets per plant (5.3), grains per panicle (110.6), test grain weight (27.4 g), dry root weight per plant (0.73 g), and total dry biomass per plant (8.26 g).